2009
DOI: 10.1534/genetics.108.094805
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila and Vertebrate Casein Kinase Iδ Exhibits Evolutionary Conservation of Circadian Function

Abstract: Mutations lowering the kinase activity of Drosophila Doubletime (DBT) and vertebrate casein kinase Ie/d (CKIe/d) produce long-period, short-period, and arrhythmic circadian rhythms. Since most ckI shortperiod mutants have been isolated in mammals, while the long-period mutants have been found mostly in Drosophila, lowered kinase activity may have opposite consequences in flies and vertebrates, because of differences between the kinases or their circadian mechanisms. However, the results of this article establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 54 publications
(145 reference statements)
1
47
1
Order By: Relevance
“…The relative lack of effect of CK1ε disruption on circadian period suggests that the primary molecular target of these inhibitors within the circadian system is CK1␦. Recent studies in flies suggest that vertebrate CK1␦ is better able to interact with fly clock proteins than is vertebrate CK1ε and that CK1␦ interacts with these fly components in a manner more functionally equivalent to Drosophila DOUBLETIME (13,28). Thus, CK1␦ may possess more conserved function within the circadian clockwork than CK1ε (13).…”
Section: Discussionmentioning
confidence: 99%
“…The relative lack of effect of CK1ε disruption on circadian period suggests that the primary molecular target of these inhibitors within the circadian system is CK1␦. Recent studies in flies suggest that vertebrate CK1␦ is better able to interact with fly clock proteins than is vertebrate CK1ε and that CK1␦ interacts with these fly components in a manner more functionally equivalent to Drosophila DOUBLETIME (13,28). Thus, CK1␦ may possess more conserved function within the circadian clockwork than CK1ε (13).…”
Section: Discussionmentioning
confidence: 99%
“…While full-length wild-type DBT-MYC (DBT WT ) (440 amino acids) exhibited robust mobility shifts in the presence of okadaic acid, none of the mutant proteins truncated within the nonconserved C-terminal domain at the indicated amino acids exhibited robust mobility shifts (Fig. 1C), demonstrating that the sites leading to mobility shifts are likely to be in the C-terminal domain (note that we have previously shown that these truncated forms are active kinases, so the lack of mobility shift does not arise from lack of kinase activity [21]). In addition, assessment of cells treated with both okadaic acid and the proteasome inhibitor MG132 did not produce extensive mobility shifts for the mutant DBTs (Fig.…”
Section: Wild-type Dbt Autophosphorylates Its C-terminal Domainmentioning
confidence: 77%
“…WT -MYC-HIS, -DBT K/R-MYC-HIS, and -CKI-V5 and pMT expressing various DBTs with deletions of the DBT C terminus (296, 332, and 387 amino acids remaining) have been described previously (5,21). Mutations of 6 serines/threonines in the DBT C terminus to alanine were generated by two successive site-directed mutageneses using a QuikChange kit (Stratagene, CA), with the following primers for rounds I and II: DBTC/alaIF, CAACATGGACGACGCGATGGCGGCCGCCAACGCGGCGAGACCG CCGTAC; DBTC/alaIR:, GTACGGCGGTCTCGCCGCGTTGGCGGCC GCCATCGCGTCGTCCATGTTG; DBTC/alaIIF, CCGCCGTACGACGC GCCGGAGCGTCGGCCTGCGATACGGATGCGG; and DBTC/alaIIR, CC GCATCCGTATCGCAGGCCGACGCTCCGGCGCGTCGTACGGCGG.…”
Section: S2 Cell Transfection and Expression Analysis Pmt-dbtmentioning
confidence: 99%
See 2 more Smart Citations